Modeling travel impedance to medical care for children with birth defects using Geographic Information Systems. Issue 10 (2nd September 2013) - Delmelle, Eric M.; Cassell, Cynthia H.; Dony, Coline; Radcliff, Elizabeth; Tanner, Jean Paul; Siffel, Csaba; Kirby, Russell S.
<x xml:space="preserve">Abstract</x> BACKGROUND Children with birth defects may face significant geographic barriers accessing medical care and specialized services. Using a Geographic Information Systems–based approach, one‐way travel time and distance to access medical care for children born with spina bifida was estimated. METHODS Using 2007 road information from the Florida Department of Transportation, we built a topological network of Florida roads. Live‐born Florida infants with spina bifida during 1998 to 2007 were identified by the Florida Birth Defects Registry and linked to hospital discharge records. Maternal residence at delivery and hospitalization locations were identified during the first year of life. RESULTS Of 668 infants with spina bifida, 8.1% (n = 54) could not be linked to inpatient data, resulting in 614 infants. Of those 614 infants, 99.7% (n = 612) of the maternal residential addresses at delivery were successfully geocoded. Infants with spina bifida living in rural areas in Florida experienced travel times almost twice as high compared with those living in urban areas. When aggregated at county levels, one‐way network travel times exhibited statistically significant spatial autocorrelation, indicating that families living in some clusters of counties experienced substantially greater travel times compared with families living in other areas of Florida. CONCLUSION This analysis demonstrates the usefulness of linking birth defects registry and hospital discharge data to examine geographic differences in access to medical care. Geographic Information Systems methods are important in evaluating accessibility and geographic barriers to care and could be used among children with special health care needs, including children with birth defects. Birth Defects Research (Part A) 97:673–684, 2013. © 2013 Wiley Periodicals, Inc.